What Happens when the Students Work in Groups? Group Dynamics in English Language Classroom - Suryani, Adi; Soedarso, Soedarso (International Journal for Educational and Vocational Studies, 2020)
EFL education shifts from teaching language core competences into promoting communicative competence and developing multiliteracies pedagogy. Through this learning mode, EFL learners can develop language, interpersonal communication, inter-cultural understanding as well as life learning skills. Group work learning assisted by technology use in EFL classroom is one of many approaches to equip EFL learners with such skills. During the process of learning in groups, EFL students experience and potentially learn social skills through their group dynamics. This study aims to explore group dynamic aspects in EFL learning: what the students experience and learn. The study adopts qualitative research methods. The data are collected through students’ narrative texts revealing their experiences in working in groups to create video. The study finds that in accomplishing group tasks, the students are learning some aspects. The first is the identification process, in which they are aligning themselves to the shared identity, emotion, goals, character of groups (self to group identification) as well as group to self identification. The second aspect is the students are learning cooperatively and collaboratively in team development process. The third aspect is learning leadership and organizational management, in which they are learning structure, norms, rules and social system in group.